Les défis de la méta-analyse pour produire des conclusions générales sur les dispositifs d’aide à la réussite dans l’enseignement supérieur - Cathy Perret; Elysa Villeneuve (Éducation et Socialisation)
Abstract : In response to the growing number of measures aimed at improving student success in the first cycle of higher education, research in the educational sciences has proliferated. However, it remains difficult to gain an overall view of the effects of these schemes: what impact do they have? to what extent? under what conditions? In this article, we discuss the value of meta-analysis in answering these questions. Widely used in medical research, this method involves re-using data from previous research to propose a critical review and an evaluative combination to identify a central trend. In the field of educational science, this method is still little used. It has many strengths, but is not without its limitations (heterogeneity of data mobilized, methodological quality of studies, etc.). If the implementation of such a method requires the determination of inclusion criteria for the primary studies mobilized, it also implies the need for a strong definition of the object studied, i.e. the systems, their effects and the contexts in which they are deployed. By showing the plurality of possible definitions, effects and contexts in which these schemes are deployed, this article proposes a methodological reflection for the implementation of future research programs mobilizing meta-analysis to study student success support schemes.